Metal chloride salts in the preparation of activated carbon and their hazardous outlook - Lee, L. Z. (Taylor and Francis Inc., 2016)
Zinc chloride (ZnCl2) is a well-known activating agent in the preparation of activated carbon, a material that is widely used in the treatment of wastewater. However, the use of ZnCl2 rendering the inevitable aquatic environmental issues due to the toxicity of metal cations. This paper highlights an overview on the latest development of metal chloride-activated carbon with special focus on the characteristics of activated carbon and the hazardous effects of metal chloride salts on human health and environment. The discussion is directed to shed some light on the feasible use of less hazardous metal chloride salts in the preparation of activated carbon.